(untitled) - Fuller, Gary (Lanham, Maryland, 2015)
An inveterate traveler and geographer extraordinaire, Fuller provides extensive background, engaging maps and photos, and thorough explanations for each intriguing trivia question. Challenging today’s global generation to truly get to know their world, his book is a delight to read and an essential antidote to our lack of geographical knowledge.
Keywords: Địa lý,Geography